From Flatland to Spaceland: Higher Dimensional Patterning with Two‐Dimensional Materials. Issue 23 (28th February 2017) - Chen, Po‐Yen; Liu, Muchun; Wang, Zhongying; Hurt, Robert H.; Wong, Ian Y.
Abstract : The creation of three‐dimensional (3D) structures from two‐dimensional (2D) nanomaterial building blocks enables novel chemical, mechanical or physical functionalities that cannot be realized with planar thin films or in bulk materials. Here, we review the use of emerging 2D materials to create complex out‐of‐plane surface topographies and 3D material architectures. We focus on recent approaches that yield periodic textures or patterns, and present four techniques as case studies: (i) wrinkling and crumpling of planar sheets, (ii) encapsulation by crumpled nanosheet shells, (iii) origami folding and kirigami cutting to create programmed curvature, and (iv) 3D printing of 2D material suspensions. Work to date in this field has primarily used graphene and graphene oxide as the 2D building blocks, and we consider how these unconventional approaches may be extended to alternative 2D materials and their heterostructures. Taken together, these emerging patterning and texturing techniques represent an intriguing alternative to conventional materials synthesis and processing methods, and are expected to contribute to the development of new composites, stretchable electronics, energy storage devices, chemical barriers, and biomaterials. Abstract : Emerging approaches to fabrication of 3D architectures are discussed, emphasizing creation of textural patterns by directed assembly of nanosheet building blocks: i) wrinkling and crumpling of 2D material films; ii) wrapping and crumpling of 2D materials around curved objects; iii) folding (origami) and cutting (kirigami) using 2D materials; and iv) 3D printing from 2D nanosheet suspensions.